Wild-type S100A3 and S100A13 restore calcium homeostasis and mitigate mitochondrial dysregulation in pulmonary fibrosis patient-derived cells - Al-Mutairy, Eid A.; Al Qattan, Somaya; Khalid, Mohammed; Al-Enazi, Azizah A.; Al-Saif, Maher M.; Imtiaz, Faiqa; Ramzan, Khushnooda; Raveendran, Vineesh; Alaiya, Ayodele; Meyer, Brian F.; Atamas, Sergei P.; Collison, Kate S.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Patients with digenic S100A3 and S100A13 mutations exhibited an atypical and progressive interstitial pulmonary fibrosis, with impaired intracellular calcium homeostasis and mitochondrial dysfunction. Here we provide direct evidence of a causative effect of the mutation on receptor mediated calcium signaling and calcium store responses in control cells transfected with mutant S100A3 and mutant S100A13. We demonstrate that the mutations lead to increased mitochondrial mass and hyperpolarization, both of which were reversed by transfecting patient-derived cells with the wild type S100A3 and S100A13, or extracellular treatment with the recombinant proteins. In addition, we demonstrate increased secretion of inflammatory mediators in patient-derived cells and in control cells transfected with the mutant-encoding constructs. These findings indicate that treatment of patients' cells with recombinant S100A3 and S100A13 proteins is sufficient to normalize most of cellular responses, and may therefore suggest the use of these recombinant proteins in the treatment of this devastating disease.